Konsep Bimbingan Dan Konseling Perspektif Pendidikan Karakter Non Dikotomik - Ussolikhah, Nakhma (Universitas Islam Bunga Bangsa Cirebon, 2020)
BK services make students able to know themselves independently, able to plan for the future better. Mistakes often occur in terms of understanding, but educators cannot be separated from their role in dealing with children who are